For the function given below determine the equation of the normal line at x = 1. f(x) = 2x^3 - 7 Find dy/dx. dy/dx = 6x^2 Let x = 1. 6(1)^2 = 6. The slope m = 6. Evaluate f(x) at x = 1. f(1) = 2(1)^3 - 7 f(1) = 2 - 7 f(1) = -5 This leads to the point of tangency (1, -5). Find the tangent line. y - y_1 = m(x - x_1) y - (-5) = 6(x - 1) y + 5 = 6x - 6 y = 6x - 6 - 5 y = 6x - 11 The slope of the normal line is the negative reciprocal of the coefficient of x. That is, m = -1/6. y - y_1 = m(x - x_1) y - (-5) = (-1/6)(x - 1) y + 5 = (-1/6)(x - 1) y + 5 = (-1/6)(x) + 1/6 y = (-1/6)(x) + 1/6 - 5 y = (-1/6)(x) - 29/6 You say?